Anti-terrorist prevention of the state - Mijalkovski Milan (Međunarodni Problemi)
The article considers the significance of the commitment of the state and its factors and forces in preventing the perpetrators of terrorism to manifest themselves in a violent way. The author takes as a starting point the fact that terrorist collectivities make great efforts to take their primary victim (state) by surprise. The response of the state should result in the efficient protection from this danger. The author considers subjective and objective limitations the anti-terrorist forces of the state are facing in the protection of the state from the terrorist surprise. This, among other things, results in porosity of the anti-terrorist prevention in some of its aspects. The volume and character of possible detrimental effects on the security of the state for the occasional porosity of the anti-terrorist prevention is treated within a separate chapter.